Recent Advances in Diazophosphonate Chemistry: Reactions and Transformations - Ullah, Saif; Hussain, Zulfiqar; Peng, Yungui (Synthesis, 2024)
Diazophosphonates function as indispensable synthetic intermediates within the domain of organic chemistry, serving as precursors for a diverse range of molecules, with potential applications as bioactive compounds. α-Diazomethylphosphonates showcase expansive reactivity and elevated levels of enantioselectivity in asymmetric transformations, especially in conjunction with suitable catalyst systems. This review compiles the latest advancements in diazophosphonate chemistry from 2016 to 2024, highlighting their reactivity and transformative potential in organic synthesis. Diazophosphonates, regarded as revolutionary compounds, exhibit unique attributes as carbene precursors, driving diverse chemical reactions such as [3+2] cycloaddition, asymmetric [3+2] cycloaddition, asymmetric [3+3] cycloaddition, and asymmetric substitution reactions. Their adaptability in functional group conversions underscores their pivotal role in various synthetic methodologies. The review highlights the growing interest in diazophosphonate reactions among synthetic chemists, fostering novel synthetic strategies and expanding their application horizons. The multifaceted utility of diazophosphonates as reagents, synthetic intermediates, precursors, and catalysts underscores their significance in modern organic chemistry and pharmaceutical applications, prompting further exploration into this dynamic field.1 Introduction2 [3+2] Cycloaddition Reactions3 Asymmetric [3+2] Cycloaddition Reactions4 Asymmetric [3+3] Cycloaddition Reactions5 Asymmetric Substitution Reactions6 Diazophosphonates as Carbene Precursors7 Diazophosphonates in the Chemistry of Fluorinated Compounds8 Other Reactions9 Future Directions10 Conclusion
Keywords: diazophosphonates; carbene precursors; synthetic intermediates; functional group conversion; cycloaddition reactions; enantioselectivity; bioactive compounds; asymmetric transformations